Intestinal Cellular Biomarkers of Mucosal Lesion Progression in Pediatric Celiac Disease - Serena Vitale; Mariantonia Maglio; Stefania Picascia; Ilaria Mottola; Erasmo Miele; Riccardo Troncone; Renata Auricchio; Carmen Gianfrani (MDPI AG, 2021)
Celiac disease (CD) is a chronic intestinal inflammation caused by gluten ingestion in genetically predisposed individuals. Overt-CD and potential-CD are the two main forms of gluten intolerance in pediatric patients with different grades of intestinal mucosa lesion and clinical management. For overt-CD patients the gluten-free diet is mandatory, while for potential-CD the dietary therapy is recommended only for those subjects becoming clinically symptomatic overtime. To date, specific early biomarkers of evolution to villous atrophy in potential-CD are lacking. We recently observed an expansion of TCRγδ+ T cells and a concomitant disappearance of IL4-producing T cells in the intestinal mucosa of overt-CD patients compared to potential-CD children, suggesting the involvement of these two cells subsets in the transition from potential-CD to overt-CD. In this study, we demonstrated that the intestinal densities of IL4+ T cells inversely correlated with TCRγδ+ T cell expansion (p < 0.005) and with the serum levels of anti-tissue transglutaminase antibodies (p < 0.01). The changes of these two cell subsets strongly correlated with mucosal lesions, according to the histological Marsh classification, as the transition from M0 to M3 lesions was associated with a significant reduction of IL4+ T cells (M0 vs. M1 p < 0.04, M0 vs. M3 p < 0.007) and an increase of TCRγδ+ T cells (M0 vs. M1 p < 0.05, M0 vs. M3 p < 0.0006). These findings strongly suggest that the detection of TCRγδ+ and IL4+ T cells could serve as cellular biomarkers of mucosal lesion and targets of novel immunomodulatory therapies for CD.